Benign Multicystic Peritoneal Mesothelioma: A Rare Condition in an Uncommon Gender - Muhammad S. Khurram; Hamadullah Shaikh; Uqba Khan; Jacob Edens; Warda Ibrar; Ameer Hamza; Awais Zaka; Roohi Bano; Tarik Hadid (Case Reports in Pathology)
Benign Multicystic Peritoneal Mesothelioma (BMPM) is a rare condition that arises from the abdominal peritoneum. Fewer than 200 cases have been reported worldwide. BMPM usually affects premenopausal women and is extremely rare in men. Many factors are suspected to contribute to its development, such as previous surgery, endometriosis, and familial Mediterranean fever. The main management is surgical resection; however, it is estimated that the recurrence rate is up to 50%. Malignant transformation is rare. We report a case series of three male patients who were diagnosed with BMPM and were treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC).